Elucidating the linkages between entrepreneurial orientation and local government sustainability performance - Deslatte, Aaron and Swann, William L. (The American Review of Public Administration)
Linking strategic management to performance has been called essential for public managers to confront pernicious environmental and community problems in the 21st century. This article examines the role that an organization$1 (Bs entrepreneurial orientation (EO) plays in the linkages between organizational capacities, strategies, and perceived performance. An EO is considered a key driver of a public organization$1 (Bs willingness to engage in risk taking, innovation, and proactivity aimed at enhancing organizational routines, decision-making, and performance. Scholars have provided empirical guidance for the antecedents and consequences of entrepreneurialism in bureaucracy, yet we know little systematically about how EO links to strategies that may affect performance in the public sector. To investigate, we employ a mixed methods design using a nationwide survey of U.S. local governments and interviews with local government managers about their experiences in sustainability programs. Quantitatively, we find evidence for environmental factors of political and administrative capacities positively influencing EO, and that strategic activities of performance information use, venturing, and interorganizational collaboration mediate the relation between EO and perceived sustainability performance. Interviews corroborate these findings and illuminate how local government managers proactively engage stakeholders, consider risk taking, build capacity, and pursue innovation in sustainability. - Reproduceds
Keywords: Entrepreneurial orientation, Local governments, Public organizations, Strategic management, Performance management, Sustainability